EFEK EKSTRAK ETANOL DAUN PEPAYA CALINA TERHADAP PROFIL DARAH TIKUS WISTAR - Haris Setiawan; Nur Rifka Istiqomah; Sri Wijayanti Wulandari (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine the effect of Papaya Calina (Carica papaya L.) leaves ethanol extract on the blood profile of Wistar rats. The study used 20 female Wistar rats (Rattus norvegicus Berkenhout, 1769), divided into 4 groups consisting of control (aquadest), Calina papaya leaves ethanol extract at a dose of 200 mg/Kg BW, 300 mg/Kg BW, and 400 mg/Kg BW for 30 days using a 1ml gastric probe. On the 31st day, blood samples were taken from the orbital sinus using a 2 ml hematocrit pipette. Blood profile parameters include erythrocyte levels, hemoglobin, hematocrit, total leukocytes, leukocyte differential, N/L ratio, and platelets. Blood samples were analyzed using a hematology analyzer to observe the levels of erythrocytes, hemoglobin, hematocrit, total leukocytes, neutrophils, and lymphocytes as well as making a blood smear (Giemsa stain) to observe eosinophils, basophils, and monocytes. All parameters were analyzed using ANOVA test and Duncan's follow-up test with a significant level of P<0.05. The results showed that the levels of erythrocytes, hemoglobin and hematocrit were significantly different between groups with the most optimum treatment at a dose of 300 mg/Kg BW. There was a significant decrease (P<0.05) in total leukocyte levels at a dose of 400 mg/Kg BW compared to the control, but there was no significant difference in all types of leukocytes. The dose of 400 mg/Kg BW increased the N/L ratio significantly compared to the control (P<0.05). Platelet counts showed no significant difference between groups (P> 0.05). The conclusion shows that the Calina papaya leaves ethanol extract at a dose of 300 mg/Kg BW can increase the number of erythrocytes, hemoglobin, and blood hematocrit of Wistar rats. The extract at a dose of 400 mg/Kg BW affected the decrease in total leukocytes and an increase in the N/L ratio, but was still in normal condition.